Bibliographic checklist of the Algerian spider fauna (Araneae) - Benhacene, Racha; Adjami, Yasmine; Hadjeb, Ayoub; Kermiche, Khamsa; Ouakid, Mohamed Laid (Zootaxa, 2023)
The present checklist of the spiders (Araneae) of Algeria is based on literature items published from 1846 to 2022. Altogether 876 species belonging to 51 families are listed. Taxonomic references are mentioned for each species, with indication of synonymous usage or taxa changes. Information about species distribution in the Algerian provinces is also provided, revealing significant disparities in knowledge about each province. Linyphiids present the highest number of known species (155) and the highest endemic richness (54 species). Eight families are represented by a single species. 227 species are known exclusively from Algeria. Moreover, a comparison was executed between the results reported in Algeria and those reported in the neighboring countries (Tunisia, Morocco, and Libya).